Analyzing the Effect of Population Density on Household Energy Consumption: A Case Study of Indonesian Provinces - Rifa Nita Sari; Sahrul Saputro; Elisabeth Beta Harwila; Rodhiah Umaroh; yuliawati yuliawati (AIBPM Publisher, 2024)
Indonesia's rapid population growth and urbanization have intensified concerns about the rising demand for energy, making it crucial to understand the relationship between population density and energy consumption for effective policymaking. This study utilizes the STIRPAT model with multiple estimation methods, including OLS, FE, RE, FGLS, and PCSE, to explore the relationship between household energy use and population density at the provincial level in Indonesia. The analysis is based on data from 2018 to 2022, focusing on household electricity and gas usage ratios as dependent variables. Independent variables include Gross Domestic Regional Product (GDRP) Per Capita, total population, population density, and the percentage of value added by GDRP. The results indicate a positive relationship between population density and household electricity and gas consumption during the study period. These findings emphasize the need for targeted and efficient energy policies to address the growing energy demand associated with population density trends